Aesthetics of iris reconstruction with a custom-made artificial iris prosthesis - Yildirim, Timur Mert; Khoramnia, Ramin; Masyk, Michael; Son, Hyeck Soo; Auffarth, Gerd U.; Mayer, Christian (PLOS ONE, 2020)
Patients with large iris defects not only suffer from functional disadvantages but also from aesthetic limitations. The aim of this study was to evaluate the aesthetic outcome of iris reconstruction using an artificial iris (AI). In this study, 82 eyes of 79 consecutive patients with mostly traumatic partial or total aniridia that underwent iris reconstruction surgery using a custom-made silicone AI (HumanOptics, Erlangen, Germany). Pre- and postoperative photographs of 66 patients were analysed subjectively and objectively. Subjective evaluation was based questionnaires. Objective evaluation included measurement of pupil centration and iris colour analysis. Averaged hues from iris areas were transferred to numerical values using the LAB-colour-system. Single parameters and overall difference value (ΔE) were compared between AI and remaining iris (RI), as well as AI and fellow eye iris (FI). Patients, eye doctors and laymen rated the overall aesthetic outcome with 8.9 ±1.4, 7.7 ±1.1 and 7.3 ±1.1 out of 10 points, respectively. Mean AI decentration was 0.35 ±0.24 mm. Better pupil centration correlated with a higher overall score for aesthetic outcome (p<0.05). The AI was on average 4.65 ±10 points brighter than RI and FI. Aniridia treatment using a custom-made artificial iris prosthesis offers a good aesthetic outcome. Pupil centration was a key factor that correlated with the amount of aesthetic satisfaction. The AI was on average slightly brighter than the RI and FI.
Gesehen am 24.09.2020